Franchthi Neolithic pottery - Vitelli, Karen D. (Excavations at Franchthi Cave, Greece Ser, 1993)
Of FCP 2.3 ContextsChapter Twelve Ceramic Subphase 2.4 (FCP 2.4); Definition; Contexts; Summary of FCP 2.4 Contexts; Chapter Thirteen Ceramic Subphase 2.5 (FCP 2.5); Definition; Contexts; Summary of FCP 2.5 Contexts; Chapter Fourteen The FCP 2/ FCP 3 Boundary; PART III The Pottery; Chapter Fifteen Introduction to the Pottery Analysis; Chapter Sixteen FCP 1 Lime Ware; Introduction; Calcareous Class: Lime Ware; Chapter Seventeen FCP 1 Sandy Ware; Noncalcareous Class: Sandy Ware; Chapter Eighteen FCP 1 Minor Wares; Noncalcareous Class: Andesite Ware; Calcareous Class: Ungritted Ware